Evaluating the effects of ozonation pretreatment on ruminal fermentation kinetics and nutritive value of wheat straw using in vitro techniques - N MAHERI-SIS; M K ESMAEILI-MARCHUBEH; A AGHAJANZADEH-GOLSHANI; A R SAFAEI; B TAVAKKOLY-MOGHADDAM (Indian Journal of Animal Sciences, 2025)
Ozone is a powerful oxidizing substance that increases lignin decomposition and improves cellulose degradation. The aim of this study is to investigate the effect of ozone pretreatment on in vitro fermentation kinetics and nutritive value of wheat straw in ruminant animals. In this study, wheat straw was pretreated with ozone for 15, 30, 45, and 60 minutes. Gas production volume was recorded at 2, 4, 6, 8, 12, 24, 48, 72 and 96 h of incubation. The digestibility of dry matter (DMD) and organic matter (OMD), metabolisable protein (MP) and metabolisable energy (ME), as well as the relative feed value (RFV) and relative forage quality (RFQ) of the feed were estimated. The results showed that the pretreatment with ozone, significantly reduced fiber components of wheat straw, including neutral detergent fibre (NDF), acid detergent fibre (ADF) and acid detergent lignin (ADL), and increased non-fibrous carbohydrates (NFC), as well as gas production in 12 to 96 hours incubation. Methane production also, significantly increased by ozonolysis pretreatment. Estimated parameters related to nutritive value including digestible energy (DE), metabolisable energy (ME), net energy for lactation (NEl), OMD, DMD, digestible organic matter in dry matter (DOMD), dry matter intake (DMI), RFV and RFQ were significantly increased by ozonation pretreatment. In an overall conclusion, it seems that ozonolysis pretreatment, particularly at the level of 60 minutes ozonation lead to increasing in vitro fermentation kinetics (by 33%) and nutritive value (by 14%) of wheat straw.